Medicina e scienza dell'uomo: Paul-Joseph Barthez e la Scuola di Montpellier Medicine and Science of Man: Paul-Joseph Barthez and the Montpellier School - Raffaele Carbone (Scuola delle Scienze Umane e Sociali. Quaderni, 2017)
This book focuses on the new anthropology elaborated by the physicians-philosophers of Montpellier in the second half of the 18th century, in particular, Paul-Joseph Barthez (1734-1806). In the wake of scepticism and empiricism, Barthez plans a science of man which rests upon physiological foundations and assimilates the respective resources of medicine and philosophical reflection. This essay first reconstructs the historical-cultural context in which the author's writings came into being; second, it examines the texts in which its science of man takes shape, by highlighting the methodology, conceptual tools and theoretical implications.